Strategi Pengembangan Profesionalisasi Guru Persefektif Membangun Motivasi Pada Mahasiswa Keguruan - I Wayan Arka (STAHN Mpu Kuturan Singaraja, 2021)
Higher education actors are required to anticipate various development dynamics and are expected to be able to adapt various programs and academic activities in line with the new paradigm in welcoming future-minded education, namely, a process that can give birth to individuals (students) who are armed with knowledge, skills, and abilities. and values that are needed to live and take part in the era of globalization. This condition forces teachers to immediately and quickly have the qualifications and competencies in order to provide optimal services to the educational community so that they are expected to be able to produce competent graduates. Teacher professional development is a basic need. In this regard, an educator should master the characteristics of students who are taught in depth with a variety of characters and approaches, master the field of source science (teaching materials), in terms of discriminatory content and pedagogical content, master a learning approach that educates and is self-reliant both concerning the design, as well as its implementation, as well as developing professional skills in a sustainable and varied manner